2022
DOI: 10.3389/fphar.2022.837890
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Renin-Angiotensin System Inhibitors on Parkinson’s Disease: A Nationwide Cohort Study

Abstract: Background: Renin-angiotensin system (RAS) inhibitors have been suggested as protective agents in Parkinson’s disease (PD). However, epidemiological evidence on the association between RAS inhibitors and the development of PD is inconsistent.Objectives: To investigate the effect of RAS inhibitors on PD risk in patients with ischemic heart disease (IHD) by type and cumulative duration of RAS inhibitors and their degree of blood-brain barrier (BBB) penetration ability.Methods: This was a propensity score-matched… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 74 publications
3
36
0
Order By: Relevance
“…The deleterious effect of AT1-AA is consistent with several previous studies showing the enhancing effect of AT1 overactivity on dopaminergic degeneration 16 , 33 , and the neuroprotective effects of drugs such as candesartan and telmisartan in PD animal models and clinical studies 15 , 16 , 33 . This is further supported by a recent study showing that the population of dopaminergic neurons most vulnerable to degeneration in PD can be identified by their high expression of the AT1 gen 11 .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The deleterious effect of AT1-AA is consistent with several previous studies showing the enhancing effect of AT1 overactivity on dopaminergic degeneration 16 , 33 , and the neuroprotective effects of drugs such as candesartan and telmisartan in PD animal models and clinical studies 15 , 16 , 33 . This is further supported by a recent study showing that the population of dopaminergic neurons most vulnerable to degeneration in PD can be identified by their high expression of the AT1 gen 11 .…”
Section: Discussionsupporting
confidence: 91%
“…The major role of the tissue RAS in inflammatory responses has been recently shown in COVID-19 pandemic, being ACE2 the entry receptor for SARS-CoV-2 and a key component for COVID-19 progression 14 . The use of AT1 antagonists such as candesartan for neuroprotection has been proposed from results in experimental models and clinical trials 15 , 16 . Interestingly, activation of endothelial AT1 receptors plays a key role in BBB disruption 17 , 18 .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, an intracellular RAS was identified in mitochondria and nuclei of dopaminergic neurons, including other RAS components such as AGTR2 and MAS receptors that may counteract the deleterious effects of AGTR1 activation 4 . Recent clinical studies also support a neuroprotective effect of AGTR1 inhibitors 3,5 . The findings of Kamath et al 1 further encourage the development of prodromal clinical trials for angiotensin receptor blockers (ARBS) that can cross the blood‐brain barrier or for molecules inhibiting AGTR1 effects, including those acting on RAS regulatory components (AGTR2, MAS) that counteract AGTR1 activation.…”
mentioning
confidence: 97%
“…A large study in Korea clearly demonstrated that ARB only had protective effects on the development and evolution of PD, whereas the statistical significance of long-term ACEI use remained elusive, a phenomenon attributed by the authors to the increased BBB permeability of the ARBs [ 60 ].…”
Section: Renin-angiotensin-aldosterone System and Parkinson’s Diseasementioning
confidence: 99%